Motivational climate, self-determination, burnout, and mindfulness in adolescent football players from a professional academy in virtual settings - Reyes-Bossio, Mario; Veran-Casanova, Natalia; de Rueda, Franco Ascenzo-Bravo; Sánchez-Villena, Andy; Delgado-Campusano, Mariel; Tutte-Vallarino, Veronica; Brandão, Regina (Frontiers in Psychology, 2026)
BackgroundThe COVID-19 pandemic shifted sports training to virtual formats, impacting athletes’ motivation, well-being, and mental health. In this context, motivational climate, self-determined motivation, mindfulness, and burnout are key factors for understanding adolescents’ psychological adjustment in football.MethodsThis study employed a cross-sectional design, with all variables collected at a single time point during mandatory virtual training. This cross-sectional study surveyed 154 adolescent football players (M = 15.9 years) from a Peruvian professional academy during mandatory virtual training. Participants completed the EDMCQ-C, SMS, MAAS-5, and ABQ. A psychological network analysis was performed in R using non-regularized partial correlations and bootstrapped stability estimates.ResultsAn empowering climate was positively associated with intrinsic motivation and mindfulness, whereas a disempowering climate was linked to extrinsic motivation and burnout. Extrinsic motivation emerged as the most central node in the network, and mindfulness functioned as a bridging node that buffered the spread of demotivation toward exhaustion. The model showed adequate stability (CS = 0.44).ConclusionEmpowering motivational climates and mindfulness protect adolescents’ psychological wellbeing, whereas controlling coaching and extrinsic motivation heighten the risk of burnout. These findings support incorporating autonomy-supportive coaching and brief mindfulness practices in youth sport training and coach education programs.